Innovations in Bio-Inspired Computing and Applications Proceedings of the 8th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2017) held in Marrakech, Morocco, December 11-13, 2017 (Advances in Intelligent Systems and Computing,, 2018)
This book highlights recent research results in Bio-Inspired Computing and Applications. It presents 33 selected papers from the 8th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2017), which was held in Marrakesh, Morocco from December 11 to 13, 2017. A premier conference in the nature-inspired computing field, IBICA is intended to bring together the world's leading researchers and practitioners interested in advancing the state of the art in biologically inspired computing, allowing them to exchange notes on a broad range of disciplines. The book offers a valuable reference guide for all researchers, students and practitioners in the fields of Computer Science and Engineering.